Pengaruh Edukasi Family Therapy Pada Keluarga Terhadap Pencegahan Perilaku Kekerasan Bullying pada Anak : Literature Review - Herman Herman; Kusbaryanto Kusbaryantlo (Ilmiah Institut Citra Internasional, 2020)
Family is lasting a a social group based on marriage and blood relations. A healthy family will contribute to the development of a healthy society. This aims to find out the effect of education system of family therapy toward prevention of violent in children. This research uses relevant Literature review which are reviewed following the search from 3 databases. They are ProQuest, ScienceDirect, and Google Scholar. The search year is limited to the last 5 years from 2014-2019 to ensure the latest included research.This review identifies 7 articles based on inclusion criteria. The article uses Quasi experimental design which are 1 article, 3 systematic reviews and integrative review, 1 quantitative, 2 qualitative, randomized controlled trial. Of the 7 articles selected, 4 articles focus on violent behavior in children and bullying and 3 articles focus on family communication towards children. With the conclution Family therapy is the of family to learn how to keep a healthy family relationship, communicate effectively with family members, and work cooperatively to solve family problems. Communication in the family becomes better when each family member can express what they don’t like and their desires to other family members and then find a solution together.